Eccentric Enactments: Naturkraft as Non-Formal Sustainability Education in the Anthropocene - Kardyb, Daniel Feldballe Støjberg (AU Library Scholarly Publishing Services, 2025)
This dissertation presents an exploration of the Danish non-formal sustainability education project Naturkraft. The Naturkraft project develops and – since 2020 – operates a nature science centre by the name Naturkraft in the Ringkøbing-Skjern Municipality on the Danish west coast. This dissertation is based on an ethnographic field study conducted in and around the Naturkraft project between February 2020 and September 2021. The focus of the exploration is to understand the Naturkraft project as a way of ’enacting’ non-formal sustainability education in the Anthropocene. Accordingly, the dissertation seeks to open new perspectives on sustainability educational thought, research, and practice in relation to Anthropocene challenges. The dissertation situates itself within the research field of environmental and sustainability education (ESE), with a particular focus on non-formal education forms and the thematization of Anthropocene issues in pedagogy and education. This implies, on the one hand, a broad understanding of ’education’ that extends beyond formal education institutions and rationales. On the other hand, it implies understanding sustainability perspectives in Naturkraft from a socioecological perspective, with theoretical attention to material, embodied, and imaginary aspects of the educational situations the project frames. Drawing on thinkers such as Deleuze & Guattari, Anna Tsing and colleagues, Timothy Morton, Elizabeth Ellsworth and George Marcus, the dissertation proposes the concept of eccentric education as a way to consider and discuss the mode of sustainability education in Naturkraft.